PERAN MEDIASI BRAND IMAGE DALAM TOURIST BOYCOTT DAN BRAND SWITCHING INTENTION: : SURVEI PADA WISATAWAN YANG MELAKUKAN BOIKOT TERHADAP BRAND GLOBAL - Elvana Amelia; Gitasiswhara (Jurnal Manajemen Perhotelan dan Pariwisata, 2026)
Increasing awareness of social and humanitarian issues influences tourists’ consumption behavior, including their tendency to engage in boycotts of global brands. This study aims to examine the relationship between tourist boycott, brand image, and brand switching intention in the context of tourist consumption. A quantitative approach was employed through a survey of 300 tourists who participated in boycotting global brands. Data were analyzed using Structural Equation Modeling (SEM) with IBM SPSS AMOS 24.0 to assess validity, reliability, and structural relationships among variables. The results indicate that boycott behavior has a positive effect on brand switching intention and a negative effect on brand image. Furthermore, brand image partially mediates the relationship between boycott behavior and brand switching intention. These findings enrich the literature on tourist behavior and provide implications for brand strategy management within the tourism industry.